FORMULATION OF CRITERIA AND SUSTAINABILITY ASSESSMENT OF COMMUNITY-BASED WATER SUPPLY PROVISION IN PERI-URBAN AREAS - Alma, Zitni
The demand for clean water in urban areas will continue to increase in line with the increasing population. However, the demand has not been matched by the number of houses connected to the clean water supply provided by the government. As a result, there are still several areas in urban areas including peri urban or suburban areas that have not received access to clean water from the government, with one of the reasons being related to the distance of the connection. So to overcome this problem, the community is provided with clean water source points by the government and then expected to be managed independently by the community. However, the next challenge is whether the water supply infrastructure that is currently available can be sustainable. Previous research that has been conducted related to the assessment of the sustainability of community-based water supply in coastal areas and urban areas with community-based management is quite different. Therefore, this study attempts to formulate criteria and assess the sustainability of community-based water supply systems in the peri urban area of Metropolitan Bandung with the difference that the management is actually carried out independently by the community without any government intervention after the provision of assistance. The analysis method that will be used is the Analysis of Hierarchical Process (AHP) to assist in obtaining value weights, later used to assess the sustainability of community-based clean water supply with a total of 17 criteria. The results of the research conducted by assessing community-based clean water supply in the peri-urban area of Metropolitan Bandung showed 69% with 12 sustainability assessment criteria already present in the Tirta Jatihandap community-based clean water supply system. However, there are still 5 criteria that are not met